A simplified method for acquisition of the parameters of Jiles-Atherton hysteresis scalar model without use of derivatives - Barbosa R. Mendes, Filomena; Leite, Jean V.; Batistela, Nelson J.; Sadowski, Nelson; Suarez, Fredy M. S. (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
Several methods have recently been proposed to identify the parameters of Jiles-Atherton model, e.g. differential evolution method, particle swarm optimization, and optimization branch and bound. In this work, it is presented a simplified method that avoids the rough calculation of derivatives, the rough calculation of integrals and avoids filtering data during the processing of the material characterization. Other advantages of proposed method are speed in the parameter calculation, the initial and anhysteretic magnetization curves and restrictions on the search space of parameters are not used, the search space of parameters is wide ranging from zero to infinity, it uses a trust region strategy to improve the robustness when the initial set of parameters is far from solution. In order to validate the method, simulated loops are compared with experimental ones.